Michailides, Constantine - (:unkn) unknown (My University, 2026)
Dr. Constantine Michailides holds a BSc, MSc and PhD in Civil Engineering from Aristotle University of Thessaloniki (AUTh), Greece. He did a PhD (2012) in Marine and Offshore Engineering in hydroelasticity of floating structures and wave energy production. Since May 2013, he joined Centre for Ships and Ocean Structures (CeSOS) and Centre for Autonomous Marine Operations and Systems (AMOS) in the Department of Marine Technology at the Norwegian University of Science and Technology (NTNU), Trondheim, Norway. In NTNU he was working as Postdoctoral Researcher mainly on projects with focus to experimental and numerical investigation of combined offshore wind turbines and ocean energy devices until January 2016 when he was appointed as a Senior Lecturer in the Marine and Offshore Engineering at Liverpool John Moores University, Liverpool, UK. ' On July 2017 Constantine started as a Lecturer (elected Faculty member/'μέλος ΔΕΠ') of Offshore Structures/Engineering in the Department of Civil Engineering and Geomatics in Cyprus University of Technology (CUT), Limassol, Cyprus. Currently in CUT he is teaching: (i) Coastal Engineering, (ii) Offshore Structures/Engineering, (iii) Water supply and hydraulic network analysis, and (iv) Law and Technical Legislation. Dr. Constantine Michailides has performed research on numerical analysis, experimental testing and structural-field monitoring of offshore and coastal structures and systems. His research focuses on global and local numerical analysis of offshore and coastal structures and systems (oil and gas, renewable energy, ports), fluid-structure interaction, wave kinematics, hydro -dynamics -elasticity, ocean energy devices, offshore wind technology, offshore combined energy systems, physical model testing, structural health monitoring, optimization, genetic algorithms and floating bridges/tunnels. Recent interests include reliability analysis for offshore engineering applications, CFD and coastal morphodynamics. Constantine is a member of national and international research, professional and funding bodies (e.g. International Symposium of Offshore and Polar Engineers/ISOPE, International Ship and Offshore Structures Congress/ISSC, Technical Chamber of Greece/TCG, ASRANeT, and Peer Review College member in Engineering and Physical Sciences Research Council/EPSRC in UK). He authored more than 70 research papers in peer reviewed journal and conference proceedings and one book in the field of coastal and offshore engineering. Constantine has an active role in different global research/professional bodies. Constantine is leader of the Marine Civil Engineering lab of Cyprus University of Technology and member of Smarten-i group (http://www.smarten-i.com/).
Keywords: energy; engineering; environmental; Global and local numerical analysis of offshore and coastal structures and systems (oil and gas, renewable energy, ports), fluid-structure interaction, wave kinematics, hydro -dynamics -elasticity, ocean energy devices, offshore wind technology, offshore combined energy systems, physical model testing, structural health monitoring, optimization